2013
DOI: 10.1093/nar/gkt942
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing analyses expands the Pseudomonas aeruginosa AmpR regulon to include small RNA-mediated regulation of iron acquisition, heat shock and oxidative stress response

Abstract: Pathogenicity of Pseudomonas aeruginosa, a major cause of many acute and chronic human infections, is determined by tightly regulated expression of multiple virulence factors. Quorum sensing (QS) controls expression of many of these pathogenic determinants. Previous microarray studies have shown that the AmpC β-lactamase regulator AmpR, a member of the LysR family of transcription factors, also controls non-β-lactam resistance and multiple virulence mechanisms. Using RNA-Seq and complementary assays, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 132 publications
7
85
0
Order By: Relevance
“…This is in accordance with the current model where, in the absence of ␤-lactams, AmpR represses ampC transcription, and when exposed to antibiotics, cells accumulate peptidoglycan catabolites (i.e., 1,6-anhydroMurNAcpeptides), changing AmpR to an activator of ampC transcription (33,46,47). In P. aeruginosa, AmpR plays a role in physiological processes and influences the expression of over 500 genes, including virulence-encoding genes and other transcriptional regulators (15,16,48). Then, AmpR appears as a global regulator, and its possible role in the virulence of ECC should be further investigated.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This is in accordance with the current model where, in the absence of ␤-lactams, AmpR represses ampC transcription, and when exposed to antibiotics, cells accumulate peptidoglycan catabolites (i.e., 1,6-anhydroMurNAcpeptides), changing AmpR to an activator of ampC transcription (33,46,47). In P. aeruginosa, AmpR plays a role in physiological processes and influences the expression of over 500 genes, including virulence-encoding genes and other transcriptional regulators (15,16,48). Then, AmpR appears as a global regulator, and its possible role in the virulence of ECC should be further investigated.…”
Section: Resultssupporting
confidence: 90%
“…In Pseudomonas aeruginosa, several works showed that AmpR is a global transcriptional regulator. It is a potential membrane-associated dimer that regulates genes involved in virulence, quorum sensing, and stress response (14)(15)(16)(17)(18). In addition, three AmpD enzymes have been found in P. aeruginosa.…”
mentioning
confidence: 99%
“…Moreover, a recent work suggested that the activation of the nitrate respiratory chain in P. aeruginosa might be a response in order to compensate for the fitness cost associated with particular antibiotic resistance mechanisms (50). Therefore, our results complement previous studies performed with the AmpR mutant that point out a link between ␤-lactamase and global regulation in P. aeruginosa (3,51,52). Indeed, although the exact CreBC regulatory mechanisms are still unknown, we demonstrate the complexity and multiregulatory processes by which P. aeruginosa controls the expression of genes of diverse functions from ␤-lactam resistance to biofilm formation or anaerobic respiration.…”
Section: Resultssupporting
confidence: 89%
“…The role of AmpR as regulator of ampC expression has been clearly established in both the Enterobacteriaceae and P. aeruginosa. Our recent work has further redefined AmpR as a major global regulator, playing an important role in acute infections through its regulation of virulence, biofilm formation, quorum sensing, and non-␤-lactam resistance (31,(39)(40)(41)87). Regulation of ampC, however, remains one of its most critical roles, as AmpC derepression is a prevalent mechanism of ␤-lactam resistance in P. aeruginosa.…”
Section: Fig 8 Stability Of P Aeruginosa Ampr Mutant Proteins Totalmentioning
confidence: 99%